2017
DOI: 10.1136/jech-2016-208145
|View full text |Cite
|
Sign up to set email alerts
|

Association of cannabis use with the development of elevated anxiety symptoms in the general population: a meta-analysis

Abstract: The findings indicate that cannabis use is no more than a minor risk factor for the development of elevated anxiety symptoms in the general population. They may inform the debate surrounding the legalisation of cannabis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 25 publications
(26 reference statements)
1
29
0
Order By: Relevance
“…Clinically significant effect sizes were determined a priori: odds ratios (ORs) of 1.5 were considered clinically meaningful differences based on a Cohen of *0.2 24 and previous meta-analyses of cannabis use and mental health outcomes, which used an OR of 1.5 as the cutoff for clinically meaningful effects. 25,26…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Clinically significant effect sizes were determined a priori: odds ratios (ORs) of 1.5 were considered clinically meaningful differences based on a Cohen of *0.2 24 and previous meta-analyses of cannabis use and mental health outcomes, which used an OR of 1.5 as the cutoff for clinically meaningful effects. 25,26…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Evidence for the predictive role of cannabis consumption on the onset of anxiety disorders is still weak. Recently, two meta-analysis of longitudinal studies ( 51 , 52 ) on the association between cannabis use and anxiety symptoms in the general population concluded that cannabis use is a minor risk factor for the development of elevated anxiety symptoms in the general population. With specific regard to the onset of SA disorder, a recent longitudinal study ( 53 ) assessing the bidirectional association between cannabis use and anxiety disorders in a population-based adult sample found a trend linking problematic cannabis use with the future development of SA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also supports an increased risk for elevated anxiety symptoms in regular cannabis users. A meta-analysis of 40 studies revealed a 1.15 increased risk of developing elevated anxiety symptoms [91]. On the other hand, individuals with social anxiety disorder are more susceptible to cannabis-related impairment and have an increased risk of developing cannabis use disorder [92,93].…”
Section: Association With Anxiety and Depressionmentioning
confidence: 99%